Analytical modeling and calculation of core grounding current in converter transformer - Zhou, Xiu; Tian, Tian; Wu, Peng; Luo, Yan; Bai, Jin; He, Ninghui; Li, Xiuguang (Frontiers in Energy Research, 2023)
In recent years, the calculation of the core grounding current of the converter transformer is difficult, low precision, and time-consuming, especially when the core is grounded by multiple points. This makes it difficult to analyze the core grounding current. To improve the accuracy of the calculation and reduce the complexity of the calculation, this paper carries out analytical calculation, simulation analysis, and experimental research on the grounding current of the converter transformer core. Firstly, a calculation method of core grounding current considering the winding connection of the converter transformer is proposed. In the implementation process, the converter transformer circuit model is established and the influence of saturation characteristics is considered, and the core grounding current is calculated and analyzed. Secondly, the grounding current of the converter transformer core is calculated by the finite element method (FEM). Finally, the proposed scheme is verified by experiments. The results show that the analytical method is close to the FEM and the experimental method, which indicates that the analytical method proposed can meet the accuracy requirements of engineering in this paper, and provides a new scheme for fast and accurate calculation of the grounding current of the converter transformer core.